Potential of curcumin-loaded cubosomes for topical treatment of cervical cancer - Victorelli, Francesca Damiani [UNESP]; Manni, Livia Salvati; Biffi, Stefania; Bortot, Barbara; Buzzá, Hilde Harb; Lutz-Bueno, Viviane; Handschin, Stephan; Calixto, Giovana; Murgia, Sergio; Chorilli, Marlus [UNESP]; Mezzenga, Raffaele (Elsevier, 2022)
Cervical cancer is one of the most common cancers affecting women worldwide. There are an estimated 570.000 new cases of cervical cancer each year and conventional treatments can cause severe side effects. In this work, we developed a platform for vaginal administration of lipophilic drugs for cervical cancer treatment. We formulated mucoadhesive cubosomes for the delivery of curcumin, a lipophilic drug for cervical cancer treatment, to increase its bioavailability and local absorption. This study tests the use of cubosomes for vaginal drug administration and assesses their potential efficiency using the CAM (chick embryo chorioallantoic membrane) model. SAXS (small-angle X-ray scattering), cryo-TEM (cryo-transmission electron microscopy), and dynamic light scattering (DLS) were employed to characterise the system. With ex vivo permeation and retention studies, we find that the curcumin released from our system is retained in the vaginal mucosa. In vitro cytotoxicity assay and cellular uptake showed an increased cytotoxic effect of curcumin against HeLa cell line when incorporated into the cubosomes. The curcumin-loaded cubosomes also demonstrated an antiangiogenic effect evaluated in vivo by the CAM model.
Keywords: Cervical cancer; Chorioallantoic membrane model; Cubosomes; DOTAP; Mucoadhesion; Vaginal administration